2002
DOI: 10.1021/la011458x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Electrochemical Studies of Ionic Liquids

Abstract: Room-temperature ionic liquids (ILs) have been proposed as alternative solvents for organic synthesis, separations, and electrochemical applications. Here, we report studies that probe the electrochemical and solvation properties of a tetraalkylammonium (methyltributylammonium bis(trifluoromethylsulfon)imide, M3BNIm) and an imidazolium (1-butyl-3-methylimidazolium hexafluorophosphate, BMIPF6) based ionic liquid. It is demonstrated that despite impurities, the cathodic limit at a Pt electrode is enhanced for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
246
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(252 citation statements)
references
References 50 publications
5
246
0
1
Order By: Relevance
“…On the other hand, neutral solutes are not as strongly coupled to their neighbors and may sample less polar, lower friction nanoenvironments, resulting in faster diffusion. The effects can also occur in the opposite directionQuinn et al 133 predicted viscosities 3.4 times higher than were observed for two ILs based on electrochemically obtained diffusion coefficients for the divalent Ru͑bpy͒ 2 2+ cation. Pulse radiolysis studies have shown that the diffusionlimited reactions of ͑anionic͒ solvated electrons with aromatic molecules in ILs are slower that those of neutral hydrogen atoms with the same substrates, reversing the trend observed in regular solvents.…”
Section: Electron and Hole Transport In Ilsmentioning
confidence: 88%
“…On the other hand, neutral solutes are not as strongly coupled to their neighbors and may sample less polar, lower friction nanoenvironments, resulting in faster diffusion. The effects can also occur in the opposite directionQuinn et al 133 predicted viscosities 3.4 times higher than were observed for two ILs based on electrochemically obtained diffusion coefficients for the divalent Ru͑bpy͒ 2 2+ cation. Pulse radiolysis studies have shown that the diffusionlimited reactions of ͑anionic͒ solvated electrons with aromatic molecules in ILs are slower that those of neutral hydrogen atoms with the same substrates, reversing the trend observed in regular solvents.…”
Section: Electron and Hole Transport In Ilsmentioning
confidence: 88%
“…The ILs have, in fact, been successfully used in many applications, including replacing traditional organic solvents in organic and inorganic syntheses, solvent extractions, liquid-liquid extractions, and electrochemical reactions as well as a medium to enhance the sensitivity of thermal-lens measurements. [23][24][25][26] A new optical sensor was reported for the determination of cyanide ion and the application of ionic liquid, as a modifier, has been introduced for constructing optical sensors. 27 In this research, an optical sensor was reported to be as a rapid, routine and selective indirect spectrophotometric determination of ascorbic acid based on its reducing ability.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ion transfer at the water|room temperature ionic liquid (W|RTIL) interface has attracted increasing attention, since the first report by Quinn et al [5]. In particular, the group of Kakiuchi has been very active [6][7][8] since their pioneering work in 2003 [9], and the first review paper on this topic was published recently [10].…”
Section: Introductionmentioning
confidence: 99%